Проблемы экономики. О структуре общества Ближнего Востока до середины II тыс. до н.э. (4. Структура государственного сектора экономики в Западной Азии. 5. Общие выводы. Структура общества и способ производства на Ближнем Востоке к середине II тыс. до н.э. - Дьяконов, И. M.
D’jakonov = Diakonoff, I. M.; Problems of Economies. The Structure of Near Eastern Society to the Middle of the Second Millennium B.C. (4. The Structure of the State Sector of the Economy in Western Asia. 5. General Conclusions. The Structure of Society and the Mode of Production in the Near East to the Middle of the Second Millennium B.C.); 1. und 2. = 794; 3. = 795; engl. Résumé.